PLANNING BUSINESS MODEL CANVAS WITH SWOT METHOD AT XYZ INSTITUTE - Nur Indah S K, RA. Iis Suci (Dinasti International Journal of Digital Business Management, 2020)
The background of this research is that every company must be able to make a new strategy that is right to be able to compete in the present and also in the future with other similar companies. The XYZ Institute is an institution that was established and operating since 1998. Based on data obtained in the last 4 years, the number of students enrolled at the XYZ Institute has increased and also declined erratically. Allegedly because the marketing planning segment is not yet right. The focus of this study is to identify elements within the Institute that deal directly with customers, in this case students. This research uses a descriptive qualitative approach, the type of research is a case study. Data collection is done by interview, observation, documentation, and questionnaire. Withusing the Businees Model Canvas (BMC) approach proposed by Osterwalder and Pigneur (2010). After the researcher identifies 9 elements in BMC, the researcher then conducts a SWOT analysis. The link between SWOT analysis and Business Model Canvas in this study is that SWOT can help identify strengths, weaknesses, opportunities and threats faced by companies in the process of implementing nine elements of BMC. The results of the BMC identification which were then analyzed through the BMC matrix showed that the XYZ Institute needs to change the pattern of marketing business strategies they currently have and make as many connections as possible with high school / vocational / STM schools throughout Jakarta specifically.